Institutional Integrity and Challenges in the Indonesian Constitutional Court Institution - Sulastri, Dewi; Arifin, Firdaus; Susanto, Anthon F; Huda, Uu Nurul; Md. Nor, Mohd Zakhiri (Fakultas Hukum, Universitas Muhammadiyah Yogyakarta, 2000)
The Constitutional Court of Indonesia of Indonesia is crucial in upholding legislative legitimacy and protecting constitutional rights. However, concerns over its integrity have arisen due to political interference, corruption, and ethical violations. This study aims to assess the integrity of The Constitutional Court of Indonesia, identify challenges it faces, and propose solutions to strengthen its credibility. Using a doctrinal legal research method, this study applies a legislative approach to analyze statutory regulations, a conceptual approach to explore institutional integrity principles, and a case approach to evaluate judicial decisions. Data collection is conducted through literature reviews and document analysis, with qualitative methods used for interpretation. The findings reveal a decline in public trust due to judicial corruption, controversial rulings, and undue political influence in judge appointments. The media and public surveys further reflect this erosion of confidence. To restore integrity, it is necessary to reinforce the legal framework, establish strict oversight mechanisms, enforce ethical standards with firm sanctions, and ensure transparency in the judicial selection process. These measures are crucial for maintaining the credibility of The Constitutional Court of Indonesia